Complete mitogenome of Parum colligata (Lepidoptera: Sphingidae) and its phylogenetic position within the Sphingidae - Li, Jun; Hu, Kunjie; Zhao, Yaqi; Lin, Ruirui; Zhang, Yaoyao; Li, Yan; Huang, Zhuoran; Peng, Shuying; Geng, Xuexia; Zhang, Haijun; Zhang, Xu; Ding, Jianhua (Zootaxa, 2019)
In this study, the complete mitochondrial DNA sequence of Parum colligata (Lepidoptera: Sphingidae: Smerinthinae) was sequenced firstly. The mitogenome is 15,288 bp in size, containing 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes (rRNAs), and an A+T-rich region. In the mitogenome, Ile, Leu2, and Phe are the most frequently used codon families, while codons GCG, TGC, GGC, CTG, AGG, and ACG are absent. The A+T-rich region is 358 bp in length including a motif ‘ATAGA’, an 18 bp poly-T stretch, three copies of a 12 bp ‘TATATATATATA’, and a short poly-A element. The nucleotides sequence of A+T-rich region is closer to Sphinginae than Macroglossinae. Phylogenetic analyses, based on the PCGs by using Maximum Likelihood (ML) and Bayesian Inference (BI) methods, generated consistent results that Smerinthinae was clustered together with Sphinginae to be the sister groups rather than Macroglossinae.